Fenomena Faktor Lingkungan Yang Menyebabkan Hikikomori Pada Masyarakat Di Jepang - Prasetya Eghy Satriatama (Vocational College of Diponegoro University, 2022)
Japan is one of the developed countries that has the best facilities for its citizens, but that does not rule out the possibility that there are no problems in the community. One of the existing problems is hikikomori. The purpose of writing this article is to find out the causes of the hikikomori phenomenon that is happening in Japan today. To examine these factors this article is written using a qualitative method with a descriptive approach. The research began by collecting data from a survey on hikikomori conducted by the Tokyo Edogawa Ward which was conducted from July 2021 to February 2022. From the survey results it was found that the most vulnerable age to experience hikikomori was aged 30-60 years. There are two causes of hikikomori in society, namely self and the environment. Self-factors that cause hikikomori include not wanting to interact with others, not used to social life, failure at work, not good at communicating with others, rarely communicating with the outside world, not fit with society, stress, trauma, feelings of discomfort or unfit for work or school, socially exhausted, shy, physically and mentally unstable. While environmental factors that cause hikikomori are bullying, difficulty finding a job, failing the school entrance exam, and long-term treatment for an illness.